A case of strongyloidiasis in pregnancy - Prasad, Madhva; Chauhan, Anahita; Chamariya, Sumit; Kuyare, Sunil; Koticha, Avani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Helminthic infections such as Strongyloides stercoralis occurs commonly in immunocompromised states. However, they can rarely occur in normal individuals also. A 23 year old multigravida presented at 39 weeks gestation with watery diarrhoea. She was evaluated and diagnosed of strongyloidiasis. Medical management was given and pregnancy outcome was successful. This case is reported because strongyloidiasis is a rare and underreported occurrence in pregnancy, which can occasionally be fatal.